2014
DOI: 10.1016/j.jmoldx.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Validation of BRAF Mutation Testing from Circulating Free DNA Using the Amplification Refractory Mutation Testing System

Abstract: Context: In 2013, an evidence-based guideline was published by the College of American Pathologists, the International Association for the Study of Lung Cancer, and the Association for Molecular Pathology to set standards for the molecular analysis of lung cancers to guide treatment decisions with targeted inhibitors. New evidence has prompted an evaluation of additional laboratory technologies, targetable genes, patient populations, and tumor types for testing. Objective: To systematically review and update t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 119 publications
1
29
0
1
Order By: Relevance
“…There was 100% concordance between tissue and urinary cfDNA genotypes assessed by droplet-digital PCR assay (ddPCR) in samples from 30 treatment-naive patients. The targetable mutation BRAF V600E was also analyzed in plasma- and serum-derived cfDNA samples from 221 patients with advanced melanoma [73]. Assay sensitivity for mutation detection was 44% in serum and 52% in plasma.…”
Section: Clinical Application Of Cfdna In Cancer Managementmentioning
confidence: 99%
“…There was 100% concordance between tissue and urinary cfDNA genotypes assessed by droplet-digital PCR assay (ddPCR) in samples from 30 treatment-naive patients. The targetable mutation BRAF V600E was also analyzed in plasma- and serum-derived cfDNA samples from 221 patients with advanced melanoma [73]. Assay sensitivity for mutation detection was 44% in serum and 52% in plasma.…”
Section: Clinical Application Of Cfdna In Cancer Managementmentioning
confidence: 99%
“…There were also significantly less off-target coverage for the PE supernatant and plasma (0.8 and 0.98%) compared to the TruSeq platform (9.3 and 3.2%). These results are very promising and application of NGS technology could extend plasma genotyping from such techniques as ARMS, 27 allele-specific PCR, COLD-PCR, and emulsion PCR to more comprehensive analysis. 8,28 Pipeline Performance Physician-friendly bioinformatics tools are crucial for successful implementation of personalized therapy selection guided by NGS.…”
Section: Liquid Biopsy Samplesmentioning
confidence: 94%
“…ThyroSeq for thyroid cancer. 13 Panels can be relatively small (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Kb capture size) that focus on well-studied mutation hotspots or much larger panels (several hundred Kb to a few Mb) that encompass mutations for which therapeutics are in the pharmaceutical pipelines as well as genomic sites that are frequently mutated and may be of clinical or pharmacodynamic relevance. 14,15 Mutation analysis of NGS raw sequence data involves a complicated series of processes that can be divided into two main parts: alignment and variant calling.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of AS-PCR is generally not below 0.1% [3, 9, 19, 36]. However, the recent development of a novel, rapid, and inexpensive AS-PCR assay reached a sensitivity of 0.005% due to the use of a PNA designed to inhibit the amplification of the wild-type allele [18].…”
Section: Technical Strategies For Ctdna Detection and Quantificationmentioning
confidence: 99%
“…Plasma is a better source of ctDNA than serum [19], especially because of the large amounts of wild-type DNA released by white cells lysis during clotting. However, discordant studies have shown that higher levels of ctDNA could be recovered from paired serum samples [9].…”
Section: Technical Strategies For Ctdna Detection and Quantificationmentioning
confidence: 99%